2014
DOI: 10.5195/jyd.2014.62
|View full text |Cite
|
Sign up to set email alerts
|

From 4-H International Youth Exchange to Global Citizen: Common Pathways of Ten Past Program Participants

Abstract: This qualitative study examined the life course of ten adults who participated as youth in the 4-H International Exchange program. The purpose of this research was to explore the pathways that led each participant to their exchange experience as a youth and how that experience set the stage for further development into an adulthood marked by cultural interest, awareness, competence and global citizenship. Using a grounded theory approach the data were analyzed through selective, open, and axial codings that el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…International experience programs (IEPs), such as International 4-H Youth Exchange (IFYE) and other programs employed by U.S CEP and international partners, can forge students' development of a global perspective early on (Boyd et al, 2001;Ingram, Smith-Hollins, & Radhakrishna, 2009;Odell et al, 2002). In prior studies, 4-H youth who participated in an IEP (a) demonstrated a developed global perspective and awareness of world issues, (b) reported higher levels of self-confidence and awareness of self and purpose, (c) were more willing to immerse themselves in another culture, (d) continued to travel abroad following the initial IEP, and (e) were more likely to pursue a career with an international focus (Arnold, Davis, & Corliss, 2014;Boyd et al, 2001;Ingram et al, 2009;Odell et al, 2002). Moreover, enhancing young peoples' global perspective may generate a ripple effect of international awareness and cooperation within an individual's microsystem of interaction (Boyd et al, 2001;Olberding & Olberding, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…International experience programs (IEPs), such as International 4-H Youth Exchange (IFYE) and other programs employed by U.S CEP and international partners, can forge students' development of a global perspective early on (Boyd et al, 2001;Ingram, Smith-Hollins, & Radhakrishna, 2009;Odell et al, 2002). In prior studies, 4-H youth who participated in an IEP (a) demonstrated a developed global perspective and awareness of world issues, (b) reported higher levels of self-confidence and awareness of self and purpose, (c) were more willing to immerse themselves in another culture, (d) continued to travel abroad following the initial IEP, and (e) were more likely to pursue a career with an international focus (Arnold, Davis, & Corliss, 2014;Boyd et al, 2001;Ingram et al, 2009;Odell et al, 2002). Moreover, enhancing young peoples' global perspective may generate a ripple effect of international awareness and cooperation within an individual's microsystem of interaction (Boyd et al, 2001;Olberding & Olberding, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In order to move Extension's international program forward, Extension educators should be aware of the organization's role in the program and should actively incorporate an international perspective into their programming (Bates, 2006;Ludwig, 1995). In light of the reported benefits of international cooperation as a mechanism for developing global perspective (Arnold et al, 2014;Boyd et al, 2001;Odell, Williams, Lawrence, Gartin, & Smith, 2002;USDE, 2012), the U.S. CEP has worked to internationalize programming through partnerships with international organizations, overseas development projects, 4-H youth outbound exchange programs, and programs to host international guests (Ludwig & McGirr, 2003;Major & Miller, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In order to move Extension's international program forward, Extension educators should be aware of the organization's role in the program and should actively incorporate an international perspective into their programming (Bates, 2006;Ludwig, 1995). In light of the reported benefits of international cooperation as a mechanism for developing global perspective (Arnold et al, 2014;Boyd et al, 2001;Odell, Williams, Lawrence, Gartin, & Smith, 2002;USDE, 2012), the U.S. CEP has worked to internationalize programming through partnerships with international organizations, overseas development projects, 4-H youth outbound exchange programs, and programs to host international guests (Ludwig & McGirr, 2003;Major & Miller, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…International experience programs (IEPs), such as International 4-H Youth Exchange (IFYE) and other programs employed by U.S CEP and international partners, can forge students' development of a global perspective early on (Boyd et al, 2001;Ingram, Smith-Hollins, & Radhakrishna, 2009;Odell et al, 2002). In prior studies, 4-H youth who participated in an IEP (a) demonstrated a developed global perspective and awareness of world issues, (b) reported higher levels of self-confidence and awareness of self and purpose, (c) were more willing to immerse themselves in another culture, (d) continued to travel abroad following the initial IEP, and (e) were more likely to pursue a career with an international focus (Arnold, Davis, & Corliss, 2014;Boyd et al, 2001;Ingram et al, 2009;Odell et al, 2002). Moreover, enhancing young peoples' global perspective may generate a ripple effect of international awareness and cooperation within an individual's microsystem of interaction (Boyd et al, 2001;Olberding & Olberding, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…These exchanges provide a fully immersive experience for the exchange student and facilitate reciprocal learning about countries and cultures for the host families and communities. It has been found that hosting a youth may have multiple impacts, including increasing the desire to host more individuals in the future, and a heightened urge to participate in international travel on the part of the host (Arnold, Davis, & Corliss, 2014). The benefits for the youth participating in exchange programs go beyond the cultural experiences to encompass a general improvement in life skills.…”
Section: Types Of International Programming In Extensionmentioning
confidence: 99%